Proteinuria and the risk of Incident atrial fibrillation according to glycemic stages: a nationwide population-based cohort study - Muhan Yeo; So-Ryoung Lee; Eue-Keun Choi; JungMin Choi; Kyung-Yeon Lee; Soonil Kwon; Hyo-Jeong Ahn; Bong-Seong Kim; Kyung-Do Han; Seil Oh; Gregory Y. H. Lip (Cardiovascular Diabetology)
Abstract Background Diabetes mellitus (DM) and proteinuria each independently raise the risk of atrial fibrillation (AF). We aimed to investigate the relationship between proteinuria and the risk of incident AF across glycemic stages. Methods A cohort of 4,044,524 individuals without prior AF and type 1 DM was selected from the 2009 Korean National Health Insurance Service health checkup data. The individuals were categorized into five glycemic stages: normal, prediabetes, new-onset DM, early DM (< 5 years), and late DM (≥ 5 years). Proteinuria was graded using a urine dipstick test. The development of incident AF was tracked until 2023. Results Overall, the cohort (mean age 47 ± 14 years, 44.8% female) showed increasing annual AF incidence rates from 2.05 to 7.22 per 1000 person-years from normal to late DM (p < 0.001). Incidence rates increased from 2.46 to 8.18 per 1000 person-years with increasing proteinuria (p < 0.001). Adjusted Cox regression models revealed a heightened AF risk with higher proteinuria across all glycemic stages (adjusted hazard ratios for urine dipstick 3+/4+: 1.58, 1.64, 2.39, 2.12, and 2.53 for normal, prediabetes, new-onset DM, early DM, and late DM, respectively). The proteinuria-AF association was more pronounced in individuals with DM than in those without DM but was similar among the new-onset and established DM groups. Conclusions Proteinuria is an independent and significant risk factor for incident AF at all glycemic stages. The risk of incident AF in patients with DM can be stratified by measuring the level of proteinuria rather than comparing the duration of DM. Tailoring clinical strategies to proteinuria level could potentially mitigate this risk, improving patient outcomes. Graphical abstract